Advances in adrenocortical carcinoma pharmacotherapy: what is the current state of the art?. (13th August 2022) - Cremaschi, Valentina; Abate, Andrea; Cosentini, Deborah; Grisanti, Salvatore; Rossini, Elisa; Laganà, Marta; Tamburello, Mariangela; Turla, Antonella; Sigala, Sandra; Berruti, Alfredo
ABSTRACT: Introduction: Surgery, followed or not by adjuvant mitotane, is the current mainstay of therapy for patients with early-stage adrenocortical carcinoma (ACC). Mitotane, either alone or in association with EDP (Etoposide-Doxorubicin-Cisplatin) combination chemotherapy, is the standard approach for patients with metastatic ACC. Areas covered: The activity of newer cytotoxic drugs, radioligands, targeted therapies, and immunotherapy, both in preclinical and clinical studies, will be reviewed in this paper. Expert opinion: ADIUVO trial revealed that the administration of adjuvant mitotane is not advantageous in patients with good prognosis. Future strategies are to intensify efforts in adjuvant setting in patients with high risk of relapse. In patients with advanced/metastatic disease, modern targeted therapies have shown significant cytotoxicity in preclinical studies; however, studies in ACC patients reported disappointing results so far. The absence of targeted agents specifically inhibiting the major molecular pathways of ACC growth is the main cause of the failure of these drugs. Since ACC is often antigenic but poorly immunogenic, the results of immunotherapy trials appeared inferior to those achieved in the management of patients with other malignancies. Radioligand therapy may also be a promising approach. Combination of chemotherapy plus immunotherapy could be interesting to be tested in the future.